Reliability modeling of fault tolerant control systems - Li, Hongbin; Zhao, Qing; Yang, Zhenyu (Zielona Góra: Uniwersytet Zielonogórski)
This paper proposes a novel approach to reliability evaluation for active Fault Tolerant Control Systems (FTCSs). By introducing a reliability index based on the control performance and hard deadline, a semi-Markov process model is proposed to describe system operation for reliability evaluation. The degraded performance of FTCSs in the presence of imperfect Fault Detection and Isolation (FDI) is reflected by semi-Markov states.
Keywords: fault tolerant control; reliability evaluation; semi-Markov processes